Efficacy of Neemraj and Beauvitech on Abundance and Distribution of Arthropod Pests in Soil and Hydroponically Grown Strawberry - Mbau, G.W; Kahuthia, R.G; Namikoye, E.S; Gichaba, S.N (International Journal of Entomology, 2025)
Strawberry is a commercially important crop which has gained global significance in terms of production and consumption. The strawberry farmers have been faced with economic losses due to attack from arthropod and phytophagus pests. To overcome this challenge, management of pests is important with reduced impact on beneficial organisms and the environment. Use of non-chemical approaches as an alternative to insecticide driven management is highly gaining popularity. Identification of the non-chemical production for management of strawberry pest such as entomopathogenic fungi and botanicals is critical. The need for compatibility of entomopathogenic fungi in crop production techniques with other insecticides to enhance efficacy is required. The interaction between these control agents could be synergistic, additive or even antagonistic. Synergistic interactions usually lead to enhanced effectiveness of the microbial control agents while reducing the adverse effects of the pesticides in combination. In this review a description of the compatibility of entomopathogenic fungus Beauvaria bassiana and botanical neem in strawberry pest management is given. The experiment involved five treatments: Neemraj, Beauvitech, Neemraj and Beauvitech, Ampligo and control. These treatments were allocated in a completely Randomized design in two separate greenhouse setups one with soil and other with pumice. The treatments were replicated four times. The data was subjected to analysis of variance (ANOVA) using the general linear model (GLM) procedure of the statistical analysis system (SAS) program, version 9.1. Tukey’s (HSD) test at P≤ 0.05 was used to separate significant means. The combination of Neemraj and Beauvitech was most effective in the management of pests in both hydroponics and soil grown media. Pest populations were reduced significantly as follows; thrips, Frankliniella spp 2.1, red spider mites Tetranychus species 11.5, tarnished plant bug Lygus species 3.0, there was 0% cricket Gryllus species damage and 0 number strawberry weevil in hydroponics cultures while in soil culture pest mean populations were: thrips 5.6, spider mites Tetranychus species 18.2, strawberry weevil (Otiorhynchus species) 7.0, tarnished plant bug 3.0 and there was 13.8% cricket Gryllus species damage on strawberry plants.
Keywords: Phytophygus pests; Beauvaria bassiana; Fragaria ananassa